2003
DOI: 10.3171/jns.2003.99.6.1028
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical anatomy of the great cerebral vein of Galen and its tributaries

Abstract: When a surgeon approaches the pineal region, several veins may hamper the access route. From posterior to anterior, these include the following: the superior vermian and the precentral or superior cerebellar veins, which drain into the posteroinferior aspect of the vein of Galen; and the tectal and pineal veins, which drain into its anterosuperior aspect. The internal occipital vein is the main vessel draining into the lateral aspect of the vein of Galen. It may be joined by the posterior pericallosal vein, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 34 publications
0
36
1
Order By: Relevance
“…Using the sitting position, gravity reduces the venous pressure, which makes the dissection of veins from the tumor easier. It has been generally reported that the precentral cerebellar vein can be sacrificed without any clinical symptoms (18,22,30). However, Kanno reported a case with thrombosis of the basal veins of Rosenthal and internal cerebral veins, which were initiated by division of the precentral cerebellar vein and followed by fatal hemorrhagic infarction (31).…”
mentioning
confidence: 99%
“…Using the sitting position, gravity reduces the venous pressure, which makes the dissection of veins from the tumor easier. It has been generally reported that the precentral cerebellar vein can be sacrificed without any clinical symptoms (18,22,30). However, Kanno reported a case with thrombosis of the basal veins of Rosenthal and internal cerebral veins, which were initiated by division of the precentral cerebellar vein and followed by fatal hemorrhagic infarction (31).…”
mentioning
confidence: 99%
“…Chaynes [1] described the anatomy of the ICVs in considerable detail. The ICVs run dorsally within the roof of the third ventricle with a mean maximal diameter of 2.7 mm.…”
Section: Discussionmentioning
confidence: 99%
“…During neurosurgical procedures, injury to the cerebral venous system can be caused by tears in the venous sinuses at craniotomy, brain retraction interfering with venous outflow, obliteration of veins or sinuses, and hemodynamic changes after extensive lesion removal [1,9] . Chaynes [1] described the anatomy of the ICVs in considerable detail.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations